Optimisation of through-thickness embedding location of Fibre Bragg grating sensor in CFRP for impact damage detection - Rocha, Helena Cristina Lopes (2021)
Aerospace composites are susceptible to barely visible impact damage (BVID) produced by low-velocity-impact (LVI) events. Fibre Bragg grating (FBG) sensors can detect BVID, but often FBG sensors are embedded in the mid-plan, where residual strains produced by impact damage are lower, leading to an undervaluation of the damage severity. This study compares the residual strains produced by LVI events measured by FBG embedded at the mid-plan and other through-thickness locations of carbon fibre reinforced polymer (CFRP) composites. The instrumented laminates were subjected to multiple low-velocity impacts while the FBG signals were acquired. The FBG sensor measurements allowed not only for the residual strain after damage to be measured, but also for a strain peak at the time of impact to be detected, which is an important feature to identify the nature and presence of BVID in real-life applications. The results allowed an adequate optical fibre (OF) embedding location to be selected for BVID detection. The effect of small- and large-diameter OF on the impact resistance of the CFRP was compared.